1991
DOI: 10.1159/000174866
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibody and Stroke: Possible Relation of Valvular Heart Disease and Embolic Events

Abstract: To establish the etiology of strokes related to the anticardiolipin antibody (Acla) syndrome and to determine the relationship of valvular heart disease and stroke in the presence of the Acla, clinical and objective characteristics of 21 patients with Acla, focal cerebral ischemic events were retrospectively analyzed. Twelve (86%) of 14 patients with stroke and 3 (42 %) of 7 patients with non-stroke cerebral ischemic events had echocardiographic evidence of left-sided valvular abnormalities. Features character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…These findings suggest that hypercoagulability may exacerbate the formation of thrombi in abnormal heart valves, thromboembolic brain injury and NPSLE. However, in situ thrombosis of small cerebral vessels is also possible [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that hypercoagulability may exacerbate the formation of thrombi in abnormal heart valves, thromboembolic brain injury and NPSLE. However, in situ thrombosis of small cerebral vessels is also possible [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an association of this syndrome with mitral or aortic valve thickening, which may be associated with mitral or aortic regurgitation [28]. Other studies have suggested, however, that certain forms of VHD stimulate generation of antiphospholipid antibodies, which in turn predispose to thromboembolic events [29,30,31]. …”
Section: Vhd Etiologymentioning
confidence: 99%
“…In addition, there is an increasing number of reports of an associa tion of APLA with coronary artery thrombo sis, bypass graft occlusion and valvular abnor malities [15][16][17][18][19][20][21][22], Investigation of the natural history of val vular endothelial lesions, especially in the non-SLE patient with APLA, has important clinical implications. In the previous issue of Cardiology, Barbut et al [23] provide addi tional evidence that patients with high titers of APLA may be at increased risk for cerebral embolic events from a cardiac source. They analyzed 21 patients with evidence of acute cerebral ischemic events who were retrospec tively selected from over 300 patients with high titers of APLA at their institution.…”
mentioning
confidence: 99%
“…Lack of stan dardization can make interpretation of study results more difficult, especially when older data are used for comparison. Barbut et al [23] did employ an assay which complies with these standards. In addition, their criteria for defining abnormal levels of antibody (IgG APLA > 5 SD above control) were quite stringent.…”
mentioning
confidence: 99%